2020
DOI: 10.3390/ph14010008
|View full text |Cite
|
Sign up to set email alerts
|

Adipose MSCs Suppress MCF7 and MDA-MB-231 Breast Cancer Metastasis and EMT Pathways Leading to Dormancy via Exosomal-miRNAs Following Co-Culture Interaction

Abstract: Globally, breast cancer is the most frequently diagnosed cancer in women, and it remains a substantial clinical challenge due to cancer relapse. The presence of a subpopulation of dormant breast cancer cells that survived chemotherapy and metastasized to distant organs may contribute to relapse. Tumor microenvironment (TME) plays a significant role as a niche in inducing cancer cells into dormancy as well as involves in the reversible epithelial-to-mesenchymal transition (EMT) into aggressive phenotype respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…Despite early detection and guideline-based treatment of breast cancer, a proportion of patients develop tumor recurrence or metastases months to years later [ 3 ]. There are different prognostic factors that, individually or in combination, may favor tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Despite early detection and guideline-based treatment of breast cancer, a proportion of patients develop tumor recurrence or metastases months to years later [ 3 ]. There are different prognostic factors that, individually or in combination, may favor tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes were discovered by Pan et al while studying the transition of reticulocytes to mature red blood cells (1), and were later defined by Johnstone et al as vesicles that containing non-essential proteins that are expelled from cells (2) following the fusion of microvesicles with the cell membranes (3). Subsequent studies showed that exosomes are released from blood cells, tumor cells, epithelial cells, mesenchymal stem cells and neuronal cells into the blood, saliva, urine and other body fluids (4-7).…”
Section: Introductionmentioning
confidence: 99%
“…However, these drugs still have deadly side effects, and more research is needed to confirm their exact value in oncology treatment. Many cancer cells, including PCa can release both pro- and anti-cancer bipartite exosomes, and adipocytes can also release exosomes that activate inflammatory responses in the tumor microenvironment and thus inhibit cancer proliferation and spread [ 148 , 149 , 150 ]. Therefore, the extraction of potential oncogenic exosomes from adipose exosomes may promote tumor targeting therapy.…”
Section: Discussionmentioning
confidence: 99%